19.2 IMPORTANCE OF ENCODING AND RETRIEVAL STRATEGY TO PREFRONTAL AND HIPPOCAMPAL DYSFUNCTION IN SCHIZOPHRENIA. (9th April 2019) - Daniel Ragland, J; Hannula, Deborah; Niendam, Tara; Lesh, Tyler; Solomon, Marjorie; Carter, Cameron; Ranganath, Charan
Abstract: Background: Episodic memory is consistently one of the most impaired cognitive domains in people with schizophrenia, and one of the best predictors of functional outcome following treatment. However, functional imaging studies have produced variable results regarding the memory networks most responsible for these deficits, with some studies documenting only prefrontal dysfunction, some studies indicating hippocampal dysfunction, and some research finding both prefrontal and hippocampal deficits. This study describes results from a series of cognitive neuroscience approaches to functional imaging that manipulate encoding and retrieval demands to illustrate when prefrontal and hippocampal regions contribute and do not contribute to memory deficits in schizophrenia. Methods: Results will be presented from three functional imaging memory paradigms using cognitive neuroscience approach to manipulate encoding and retrieval demands to identify when prefrontal and hippocampal deficits were, and were not, present people with schizophrenia relative to healthy controls. The first (Rehearse/Reorder) was an fMRI study in 19 controls and 20 patients that manipulated item versus relational processing demands during a working memory delay. The second (RiSE) was an fMRI study of 52 patients and 57 controls that manipulated processing demands during both episodic encoding (item versus relational) and retrieval (recollection versus familiarity). Finally, a third study (Eye Movement Memory) obtained simultaneous eye tracking and fMRI data in a sample of 26 controls and 24 patients while they tried to detect either item or relational changes in complex scenes. Results: When memory was tested in Study 1, patients had disproportionate deficits in the relational reorder condition versus the item-specific rehearse condition, with no group difference during item rehearsal, and a specific reduction on dorsolateral prefrontal cortex (DLPFC) during relational processing. Study 2 found that memory deficits depended upon both encoding and retrieval demands, with unimpaired familiarity performance following item versus relational encoding, and recollection deficits regardless of the encoding condition. Encoding results replicated Study 1 in showing a specific DLPFC deficit for relational but not for item encoding. Moreover, hippocampal dysfunction was only found in the relational or associative memory retrieval conditions. Finally, Study 3 found that patients had an unimpaired eye-movement memory effect for item but not relational changes in the scene. Hippocampal activation in patients was abnormally increased in anterior hippocampus for item changes but reduced in posterior hippocampus for relational changes. Conclusions: These results help to reconcile what has, at times, been an inconsistent story regarding prefrontal and hippocampal dysfunction in people with schizophrenia. Convergent results suggest that prefrontal dysfunction is most likely when patients are required to maintain or encode information in an associative or relational versus item specific manner. If patients are allowed to rely on these item specific representations to retrieve information based upon a sense of familiarity, they are also less likely to demonstrate hippocampal deficits than if they are required to retrieve relational information to support recollection. Finally, the presence of hyper- versus hypo-activation of the hippocampus may follow a longitudinal gradient, with reduced activation more likely in posterior hippocampus, and increased activation more likely in anterior hippocampus both in task and in resting-state conditions.